Asset pricing and energy consumption risk. (30th July 2019) - Lim, Ashley; Lan, Yihui; Treepongkaruna, Sirimon
Abstract: This paper proposes energy consumption in the US as a new measure for the consumption capital asset pricing model. We find that (i) industrial energy growth produces reasonable values for the relative risk aversion coefficient and the implied risk‐free rate; (ii) compared to alternative consumption measures, industrial energy performs well in explaining the cross‐sectional variation in stock returns with the lowest implied risk aversion and pricing errors; (iii) the industrial energy consumption risk model performs equally well as the Fama–French three‐factor model in the cross‐sectional asset pricing tests; and (iv) total energy consumption risk is priced in the presence of the Fama–French factor risks.